Clear Cell Adenocarcinoma of the Renal Pelvis in a Male Patient - Sarawut Kongkarnka; Pruit Kitirattakarn; Hironori Katayama; Surapan Khunamornpong (Case Reports in Pathology)
Carcinoma of the renal pelvis is an uncommon renal neoplasm. Clear cell adenocarcinoma in the urinary tract is rare and has a histomorphology resembling that of the female genital tract. We herein present a case of clear cell adenocarcinoma of the renal pelvis, which is the first example in a male patient to our knowledge. A 54-year-old man presented with right flank pain. The tumor was associated with renal stones and hydronephrosis and invaded into the peripelvic fat tissue with regional lymph node metastasis. The patient died of metastatic disease six months postoperatively. Histologically, the tumor showed complex papillary architecture lined with clear and hobnail cells. Clear cell adenocarcinoma of the renal pelvis may pose a diagnostic challenge on histological grounds, particularly in the distinction from renal cell carcinoma. The immunohistochemical stains could help confirm the diagnosis. Due to its rarity, an effective treatment regimen remains to be determined.